2021
DOI: 10.1016/j.socscimed.2021.114324
|View full text |Cite
|
Sign up to set email alerts
|

Good night: Experimental evidence that nighttime curfews may fuel disease dynamics by increasing contact density

Abstract: Background Nighttime curfews have been discussed and implemented in many countries as a means of controlling the COVID-19 pandemic. However, there is evidence that such curfews have little or no effect on disease dynamics when other measures such as bans on gatherings or business and school closures are already in place. There are two possible explanations for this. First, nighttime curfews may elicit reactance—a feeling of anger that drives non-adherence; second, nighttime curfews may motivate pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…They do not seem to increase incidences. The latter result seems to be important in connection with recent research based on experimental data 16 and mobility data 17 , respectively, which show that night curfews might fuel disease dynamics.…”
Section: Discussionsupporting
confidence: 58%
“…They do not seem to increase incidences. The latter result seems to be important in connection with recent research based on experimental data 16 and mobility data 17 , respectively, which show that night curfews might fuel disease dynamics.…”
Section: Discussionsupporting
confidence: 58%
“…These studies do not measure the resulting congestion in the essential businesses, but this is likely to be high, resulting in greater risk of virus spread. Importantly, recent studies show that early evening curfews backfired in Toulouse (Dimeglio et al 2021), had no effect in Hesse (Haas et al 2021) and may elicit reactance (Sprengholz et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Second, as these curfews do not affect daytime activities, they may not be effective in fighting the spread of Covid-19. They might be even counterproductive if they increase contact density during earlier hours of the day [32] . Generally, governments should not implement ineffective measures with substantial side-effects.…”
Section: Introductionmentioning
confidence: 99%
“…Sprengholz et al [32] examine public perceptions of nighttime curfews: The majority of participants in their survey did not perceive nighttime curfews as an effective measure to contain the pandemic and stated that they would not reduce private contacts due to a nighttime curfew. A substantial share of participants reported that they would rather shift a private dinner meeting forward in time, suggesting that nighttime curfews may increase contact density in the hours of the day when the curfew is not in place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation